STRATEGI TAHFIDZUL QUR’AN MELALUI KAIDAH TURKI UTSMANI DI UICCI (UNITED ISLAMIC CULTURAL CENTER OF INDONESIA) SULAIMANIYAH KERTOSONO NGANJUK - Laili, Alfi Zulfiatul; Masruroh, Laily (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
The method is definitely needed in memorizing the Qur'an, the method itself is a tool to achieve success. There are lots of methods of memorizing the Al-Qur'an, namely memorizing the Al-Qur'an from chapters 1 to 30, basically what we encounter in many Islamic boarding schools uses the same method as the wahdah method, Talaqqi and many other methods. However, at UICCI (United Islamic Cultural Center Of Indonesia) Sulaimaniyah Kertosono Nganjuk is different from other methods which of course have the same goal, namely to instill faith and piety in the younger generation who memorize the Al-Qur'an. Therefore, the objectives of this study are: 1) To acquire knowledge of Al-Qur'an memorization strategies at UICCI (United Islamic Cultural Center Of Indonesia) Sulaimaniyah Kertosono Nganjuk. 2) Knowing the strategy of memorizing the Qur'an using the Ottoman Turkish method at UICCI (United Islamic Cultural Center Of Indonesia) Sulaimaniyah Kertosono Nganjuk. 3) Gaining knowledge about the factors that influence the memorization of the Qur'an with the Ottoman Turkish method. This study uses a qualitative method with an interactive type and information approach. From the results of the study it can be concluded that the strategy of using the Ottoman Turkish method is a round system and consists of 20 rounds, before memorizing students are also required to master the makharijul letters until they reach the desired criteria. Because of the uniqueness of this method, students feel bored because basically every day they will change chapters.